Analyzing the place and function of anthropology in paradigm-oriented methodology - Parastoo Mesbahi Jamshid; Mohammad ali Abdolahi (حکمت اسرا, 2024)
The central paradigm is a theoretical framework for research in natural and human sciences. In this methodological approach, the place of epistemology and to some extent ontology in the research process is discussed, but anthropology is not independently considered by methodologists. The purpose of this research is to introduce and evaluate the paradigm-oriented approach in research methodology and outline the position of anthropology in methodology. The research method is descriptive-analytical. The findings indicate that since the research methodology is based on epistemology, and according to Allameh Javadi Amoli's opinion, epistemology is related to anthropology, it is necessary to independently consider humans in the methodology. Science should be paid. Anthropological attention puts important capacities in front of scientific knowledge, and the attitude about the nature of science, the method of knowledge and construction of theory is brought more clearly.